Wave speeds in relativistic warm plasmas - Salvatore Pennisi (Le Matematiche, 1991)
A recently obtained warm plasma model is here considered and the speeds of propagation of the discontinuity waves are calculated. These speeds, relative to the fluid, are 0, ±\sqrt{7/15}ε ,±\sqrt{3/5}ε, ±\sqrt{1/3}, where ε is the smallest parameter invariantly related to temperature. Explicit expressions are also shown for the eigenvectors.